2017
DOI: 10.1007/s10457-017-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

How is agroforestry perceived in Europe? An assessment of positive and negative aspects by stakeholders

Abstract: Whilst the benefits of agroforestry are widely recognised in tropical latitudes few studies have assessed how agroforestry is perceived in temperate latitudes. This study evaluates how stakeholders and key actors including farmers, landowners, agricultural advisors, researchers and environmentalists perceive the implementation and expansion of agroforestry in Europe. Meetings were held with 30 S. García de Jalón (&) Á P. J. Burgess Á A. Graves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 28 publications
1
48
0
1
Order By: Relevance
“…By contrast the improvement of biodiversity, landscape aesthetics, soil conservation and animal welfare were given low priorities compared to those reported by Garcia de Jalón et al (2017). The most important economic benefits were identified as lower business risk due to diversification and the production of higher quality crops and timber.…”
Section: Prioritisation Of Agroforestrymentioning
confidence: 74%
See 1 more Smart Citation
“…By contrast the improvement of biodiversity, landscape aesthetics, soil conservation and animal welfare were given low priorities compared to those reported by Garcia de Jalón et al (2017). The most important economic benefits were identified as lower business risk due to diversification and the production of higher quality crops and timber.…”
Section: Prioritisation Of Agroforestrymentioning
confidence: 74%
“…The greatest opportunities were related to the availability of subsidies and assistance from extension services, and low market opportunities and lack of subsidies were seen as the greatest risks. Garcia de Jalón et al (2017) in a pan-European study and Camilli et al (2016and Camilli et al ( , 2017 in a pan-Italian study also reported that the need for national demonstration sites and education programs to support the uptake of agroforestry. They cite the work of Pannell (1999) who identifies that a farmer considering agroforestry must i) have the information about the system, ii) be satisfied that it can be trialled, iii) perceive that it is worth trialling, and iv) and that it can support the objectives of the farm business, particularly profit.…”
Section: Prioritisation Of Agroforestrymentioning
confidence: 97%
“…Agroforestry is the incorporation of woody elements on agricultural fields; it simultaneously generates food, fodder, and woody material (Somarriba 1992;European Commission 2013). Moreover, agroforestry can provide ES and multi-environmental functions such as erosion control, reduced nutrient loss, and carbon storage (Torralba et al 2016) and is thus valued by farmers (García de Jalón et al 2018a;Rois-Díaz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The last hypothesis assumed that the stakeholder group membership determined the answer in relation to forest certification and sustainability. Past research has shown that stakeholder perceptions and opinions can differ depending on different interests and needs [21,49].…”
Section: Introductionmentioning
confidence: 99%